Clinical Characteristics and Service Use of Incarcerated Males with Severe Mental Disorders: A Comparative Case-Control Study with Patients Found Not Criminally Responsible. (1st August 2014) - Dumais, Alexandre; Côté, Gilles; Larue, Caroline; Goulet, Marie-Hélène; Pelletier, Jean-François
<x xml:space="preserve">Abstract</x> Since the drop in the bed capacity of civil psychiatric hospitals, an increase in the bed capacity of forensic psychiatric care and prison units has been reported in the United States and Europe. However, in Canada, a decrease in the number of people with severe mental illness (SMI) during the last two decades in penitentiaries has been reported. At the same time, an increase in individuals found not criminally responsible on account of mental disorder (NCRMD) was observed in forensic hospitals. The aim of this study is to compare incarcerated severely mentally ill (I-SMI) individuals with forensic-hospitalized SMI individuals in terms of their clinical profiles and service use in the province of Quebec (Canada). A case-control study design was selected using a sample of 44 I-SMI individuals and 59 forensic-hospitalized SMI individuals. Important findings include the following: I-SMI persons had less schooling; they more often reported suicide attempts and violent and non-violent crimes; and they had a higher level of comorbidity involving Cluster B personality disorders and substance-use disorders. Forensic-hospitalized SMI persons were more likely to have been receiving psychiatric follow-up before hospitalization. The final logistic regression model showed that lifetime suicide attempts, non-violent crimes, and psychopathic traits were higher among I-SMI individuals than among forensic-hospitalized SMI individuals. In contrast, receiving regular psychiatric follow-up was associated with forensic-hospitalized SMI individuals. Differences in psychopathological characteristics and the use of mental health services were found for I-SMI persons. More research is needed to determine which new initiatives might be efficacious in addressing the mental health needs of I-SMI individuals.